Characterization of Beliefs and Imaginaries of University Students on the Assessment in Mathematics - Penagos, Mauricio; Osorio-Amaya, Elkin Alejandro; Morales-Romero, Lina Fernanda (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article shows the characterization of the beliefs and imaginaries built by the university students of the B. Sc. in Mathematics teaching training program about evaluation. This is done based on the systematic qualitative analysis of the subjects' discourse, which was obtained through two interviews and two surveys carried out throughout an academic semester. The beliefs were categorized into three groups: the quantification of knowledge, the communication of the teacher and the didactics of the evaluation. In addition, the imaginary that students build about this process became tangible through a graphic representation generated from the systematic analysis developed. For students, this process is integrated into their educational process, it is presented in a clear and concise way, used to quantify their performance while feeding back their development, which lacks didactic characteristics and represents challenges, anxieties, uncertainties and confusion.